2005
DOI: 10.1128/ec.4.1.36-45.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis Reveals Localization ofSaccharomyces cerevisiaeProtein Kinase C to Sites of Polarized Growth and Pkc1p Targeting to the Nucleus and Mitotic Spindle

Abstract: The catalytic activity and intracellular localization of protein kinase C (PKC) are both highly regulated in vivo. This family of kinases contains conserved regulatory motifs, i.e., the C1, C2, and HR1 domains, which target PKC isoforms to specific subcellular compartments and restrict their activity spatially. Saccharomyces cerevisiae contains a single PKC isozyme, Pkc1p, which contains all of the regulatory motifs found in mammalian PKCs. Pkc1p localizes to sites of polarized growth, consistent with its main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 63 publications
(63 reference statements)
5
68
0
1
Order By: Relevance
“…Mutants in the MAPK cascade do not share these pkc1 phenotypes. Finally, the demonstration that the N-terminal C2-like domain of Pkc1 localizes to the mitotic spindle (Denis and Cyert 2005) supports the notion that this kinase has a target at the mitotic apparatus.…”
Section: Rho1 Activation During Cytokinesissupporting
confidence: 51%
See 1 more Smart Citation
“…Mutants in the MAPK cascade do not share these pkc1 phenotypes. Finally, the demonstration that the N-terminal C2-like domain of Pkc1 localizes to the mitotic spindle (Denis and Cyert 2005) supports the notion that this kinase has a target at the mitotic apparatus.…”
Section: Rho1 Activation During Cytokinesissupporting
confidence: 51%
“…Pkc1 becomes delocalized during G2 phase and finally relocalized at the mother-bud neck during mitosis, a transition that requires an intact septin ring (Denis and Cyert 2005). A molecular dissection of Pkc1 suggested that each regulatory subdomain was responsible for localizing a pool of Pkc1 to specific subcellular sites (Denis and Cyert 2005), knowledge that may contribute to our understanding of its functions beyond activation of the MAPK cascade.…”
Section: Pkc1 and The Cwi Mapk Cascadementioning
confidence: 99%
“…Later in the cell cycle, it becomes delocalized and finally relocalized at the mother-bud neck. The neck localization of Pkc1 requires an intact septin ring (64). A recent molecular dissection of Pkc1 suggested that each domain was responsible for localizing a pool of Pkc1 to various subcellular sites (64).…”
Section: Rho1: Master Regulator Of Cwi Signalingmentioning
confidence: 99%
“…These include the GEF Rom2 and its target GTPase Rho1 (Figure 2) (see Yoshida et al , 2009 and references therein). The latter organizes the actin cytoskeleton via its interaction with formins and also functions as an activator of the central CWI component Pkc1, which also localizes to the bud neck during cytokinesis (Andrews and Stark , 2000 ;Denis and Cyert , 2005 Actomyosin ring…”
Section: Cell Wall Integrity Signaling At the Yeast Bud Neckmentioning
confidence: 99%